Studies on Germination of Sandal (Santalum album Linn.) Pre-treatment of Sandal Seeds - Nagaveni, H. C.; Srimathi, R. A. (Indian Forester, 1981)
Sandal (Santalum alhum Linn.) seeds were pre-conditioned to increase the rate and percentage or germination and bring down the dormancy period, seeds were treated with hot and cold water and subjected to mechanical and chemical scarification. Under chemical Scarification, alcohol and sulphuric acid were used. Results show that the rate percentage of germination increased and dormancy period is brought down by acid scarification.